Zooproblematica and mollusca from the Lower Cambrian Meishucun section (Yunnan, China) and taxonomy and systematics of the Cambrian small shelly fossils of China - Parkhaev, P. Yu; Demidenko, Yu. E. (Paleontological journal, 2010)
The monograph presents the results of the study of the Cambrian small shelly fossil fauna of the Meishucun Locality (east of Yunnan Province, China), the reference section for the Cambrian stratigraphy and paleontology of China and the stratotype of the Meishucunian Regional Stage. This publication contains a monographic description of 66 species and 52 genera of zooproblematica and mollusks and an annotated checklist of the small shelly fossil species of the Cambrian of China. The checklist includes 744 nominal species (among them 508 species names are zooproblematica, 220 species names are mollusks, and 16 names represent other groups of organisms). A taxonomic revision of all mollusk and zooproblematic taxa that have ever been described from the Cambrian of China is made at the species and generic levels. We propose that, of the 508 checklisted species of zooproblematica, 221 species should be considered valid, 80 of them are considered as tentatively valid, whereas of the 220 checklisted species of mollusks, 92 species can be considered valid. It was found out that 28 species names of zooproblematica and 7 species names of mollusks should be considered as nomina nuda, since their descriptions do not satisfy the availability criterion. We have to consider 20 species of mollusks and 18 species of zooproblematica as nomina dubia, because these taxa have been described based on unsatisfactory or fragmentary preserved material lacking any diagnostic features. Based on taxonomic work, it has been shown that the great number of synonymous taxa resulted in a more than double overestimation of the real value of the nominal species biodiversity of the Cambrian small shelly fossil fauna of China. The following new taxa are described, i.e. genera: Hexagonellus Demidenko, gen. nov.; Asiapatella Parkhaev et Zhegallo, nom. nov.; Dorispira Parkhaev, gen. nov.; and species: Platyspinites elegans Demidenko, sp. nov.; Mongolodus sulcus Demidenko, sp. nov.; Hexagonellus kuzminae Demidenko, sp. nov.; Halkieria wangi Demidenko, sp. nov.; Asiapatella sinuata Parkhaev, sp. nov.; Pseudoscenella levigata Parkhaev, sp. nov.; Trifistulella tortilis Demidenko, sp. nov. Based on the analysis of biostratigraphic and chemostratigrahic data, we propose the correlation of the Upper Precambrian-Lower Cambrian boundary deposits of the Siberian Platform and Yangtze Platform. According to this correlation, the base of the Tommotian Stage corresponds to the level within the middle of the Zhongyicun Member of the Zhujiaqing Formation. The monograph contains an extensive bibliography of 379 publications on the subject.